Enhancing polyol/sugar cascade oxidation to formic acid with defect rich MnO2 catalysts - Hao Yan; Bowen Liu; Xin Zhou; Fanyu Meng; Mingyue Zhao; Yue Pan; Jie Li; Yining Wu; Hui Zhao; Yibin Liu; Xiaobo Chen; Lina Li; et al. (Nature Communications, 2023)
Abstract Oxidation of renewable polyol/sugar into formic acid using molecular O2 over heterogeneous catalysts is still challenging due to the insufficient activation of both O2 and organic substrates on coordination-saturated metal oxides. In this study, we develop a defective MnO2 catalyst through a coordination number reduction strategy to enhance the aerobic oxidation of various polyols/sugars to formic acid. Compared to common MnO2, the tri-coordinated Mn in the defective MnO2 catalyst displays the electronic reconstruction of surface oxygen charge state and rich surface oxygen vacancies. These oxygen vacancies create more Mnδ+ Lewis acid site together with nearby oxygen as Lewis base sites. This combined structure behaves much like Frustrated Lewis pairs, serving to facilitate the activation of O2, as well as C–C and C–H bonds. As a result, the defective MnO2 catalyst shows high catalytic activity (turnover frequency: 113.5 h−1) and formic acid yield (>80%) comparable to noble metal catalysts for glycerol oxidation. The catalytic system is further extended to the oxidation of other polyols/sugars to formic acid with excellent catalytic performance.